Institutional change for creating capacity and capability for sustainable development: A club good perspective - Joost Platje (OrdnungsPolitisches Portal (OPO), 2011)
Although the socio-economic development of many nations during the last two centuries has been very impressive, there are many issues questioning the sustainability of this development. Questions have been raised whether increased consumption will lead to increased happiness, or whether people will become more dependent on growth (Galbraith, 1958). While the so-called consumption society may lead to questionable results for social welfare, the increased use of natural resource and problems of waste, pollution, lack of regeneration of renewable resources and too slow progress in finding substitutes for non-renewable resources pose increasing threats for environmental sustainability (Boulding, 1966; Rao, 2000). These issues are slowly being recognized. The focus in this article is on the need for institutional change for entering a path of more sustainable (or, less unsustainable) development in the context of the seemingly infinite need for increased production and welfare. Arguments will be provided that the New Institutional Economics (NIE) may be useful in creating a theory of institutional change, strengthening society's capacity and capability for sustainable development (SD). However, without changing paradigms (worldviews) that growth is necessary and, in combination with technological advance, a mean to solve social and environmental problems, there are incredible challenges in entering a path of SD. First, some conditions for NIE to become a theory on society's capacity and capability for SD will be discussed in the context of its current focus on economic and environmental issues. Then, the notion of institutional capital will be developed and some of its determinant presented (value in the public domain, institutional strength, good governance, an institutional equilibrium). The level of transaction costs and assignment of property rights seem to be crucial for the process of institutional change. Finally, it will be argued that with the current techno-centric paradigm, when technological advance is too slow, there exists a danger that SD will become, at most, a kind of club good.
Keywords: 330; institutional change; institutional capital; institutional economics; sustainable development; club good; Nachhaltige Entwicklung; Klubtheorie; Institutioneller Wandel; Neue Institutionenökonomik